A legal analysis on the crime of an attempt to rape in the penal code / Efa Sakinah Razak … [et al.] - Razak, Efa Sakinah; Mohd Razali, Izzatul Najwa; Hakim, Norazwa Rokmal; Rahim, Siti Nur Rusydah (2014)
An attempt to rape is considered as a sexual crime towards women. In spite of the fact that the actual commencement of rape is not successful in this act, an attempted rape is still regarded as a serious offence that violates the dignity of a woman. It is a felony that is worse than other sexual harassments usually faced by females. An attempted rape indicates how close a man was in fulfilling his illicit desire to have a sexual intercourse with the female. Nevertheless, there exists no specific provision governing this particular act in the Malaysian Penal Code. There are views that claim although there is an absence of such specific provision, the existing laws are sufficient enough to cover this offence. This study is done to determine whether such claims are true and subsequently answer the issue of whether there is a need for the Penal Code to be amended in relates to the crime of attempt to rape.